Performance evaluation of beacon enabled IEEE 802.15.4 network with downlink and uplink traffic and limited retransmission. (1st January 2015) - Parsa, M.; Motamedi, S.A.; Safdarkhani, H.; Maadani, M.
Nowadays, wireless communication is a developing technology. IEEE 802.15.4 is the commonly used standard in low–data–rate and low–power applications. In real–time communications, quality of service is an important issue where delay parameter plays a crucial role. In this paper, at first a novel Markov model has been proposed for the IEEE 802.15.4 standard considering limited retransmission and both uplink and downlink traffics at the same time. Then based on the developed model and using queuing theory, the average transmission delay of a packet is derived. It is shown using numerical simulations that the behaviour of the proposed model is close to the IEEE 802.15.4 protocol and the average delay derived from mathematical expressions and Markov simulations are really close to each other.